Development of coordinating algorithm for rendezvous task of mobile robots - Ng, Jin Siang (2023)
The coordination of mobile robots is a crucial component in a variety of applications, including search and rescue, environmental monitoring, and transportation. It is essential that the robots work together to achieve a common goal efficiently and safely. In this project, the focus was on the rendezvous task, which involves bringing multiple robots to a common location. To accomplish this task, a coordinating algorithm was developed that allows the robots to work together in a distributed manner. Each robot has a limited view of the environment, and they communicate with their neighbouring robots to share information about their current position. The proposed algorithm was developed using MATLAB and implemented within ROS2, which are widely used in the robotics industry. The algorithm ensures that all robots converge to the rendezvous point while avoiding collisions with each other. It achieves this by selecting a leader or multiple leaders and then having all other robots converge towards the position of the leader, based on the information received from neighbouring robots. Overall, the proposed algorithm provides an efficient solution for the coordination of mobile robots in the rendezvous task, where the algorithm is capable of handling different group scenarios and is coordinate-free. It has the potential to be used in a wide range of applications, such as flocking control, making it a valuable contribution to the field of robotics.